Phytochemical Profiling and Hemostatic Potential of Iris domestica Fruit Extract for Wound Bleeding Control - Jon Kenedy Marpaung; Manuppak Irianto Tampubolon; Adiansyah Adiansyah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Uncontrolled bleeding remains a major challenge in wound care, particularly in emergency and resource-limited settings. Limitations of synthetic hemostatic agents, including high cost, side effects, and limited access, have driven interest in plant-based alternatives. Iris domestica contains bioactive metabolites with astringent and wound-healing properties. This study aimed to characterize its phytochemical constituents and assess the hemostatic activity of its fruit extract. Methodology: Phytochemical screening was conducted on powdered simplicia, ethanol extract, and solvent fractions (n-hexane, ethyl acetate, and aqueous). Antibacterial activity was evaluated using the agar well diffusion method against Gram-positive and Gram-negative bacteria. Hemostatic activity was assessed through in vitro clotting time and in vivo bleeding time assays in rodents, grouped into negative control (saline), positive control (standard agent), and extract-treated groups at varying concentrations. Data were analyzed using one-way ANOVA with Tukey’s post hoc test (p < 0.05). Findings:  Phytochemical analysis showed that the ethanol extract and ethyl acetate fraction contained alkaloids, flavonoids, glycosides, saponins, and tannins, with no triterpenoids detected. The ethanol extract exhibited dose-dependent antibacterial activity, with the highest inhibition against Staphylococcus aureus (12.70 mm at 250 mg/mL). Hemostatic assays revealed significantly reduced clotting and bleeding times compared to the negative control (p < 0.05), with activity comparable to the positive control, indicating strong hemostatic potential. Contributions: I. domestica fruit extract exhibits significant hemostatic activity, likely mediated by tannins via protein precipitation and vasoconstriction, with synergistic contributions from alkaloids and saponins. The inclusion of appropriate controls strengthens this evidence. These findings highlight its potential as a natural alternative to conventional hemostatic agents and warrant further bioassay-guided isolation and safety evaluation.